Analisis Kebutuhan Dasar Psikologis Ditinjau dari Aspek Kompetensi, Keterkaitan, dan kemandirian - Ranni Rahmayanthi; Eka Kurniawati; Fransiskus Nurseto; Syarifuddin Dahlan (JURNAL KONSELING GUSJIGANG, 2022)
The purpose of this study is to analyze aspects of the psychological basic needs of students. The research sample is a student population of the Department of Education of 230 students, consisting of four study programs, namely PGSD, PGPAUD, Penjas, and Guidance and Counseling. The research instrument used is the Adolescent Students' Basic Psychological Needs at School Scale (ASBPNSS). The results of the Anacova test on aspects of independence, interrelationship, and competence towards the fulfillment of basic psychological needs in students are F = 45.17 (0.05). Thus, it can be concluded that the variables of competence, interconnectedness, and independence are all congruent. All three have a significant relationship to the fulfillment of basic psychological needs of students.